Zebre, raggi di luna e storie di fate. Riflessioni sul pensiero magico - Gebhardt, Eva; Giorgini, Luca (Il sogno della farfalla, 2011)
Magic thought represents a way of thinking which is different from rational logic and is, classically, thought to be present in some primitive cultures, in some psychiatric pathologies but also in the child and in some emotional states of the adult. This article attempts to define the differences which magic thought presents in the above-mentioned contexts and make a distinction between it and intuition. In the latter, in fact, the knowledge obtained without the help of rational logic is correct because it is not spoilt by an aspect of religious alienation which is however present in magic thought. Through the study of the dynamic drive of the disappearance fantasy we then explore the idea that the constitutive nucleus of magic thought does not correspond to a pathological way of thinking but on the other hand, is characterized by a deeply human and physiological dimension present in the early stages of the lives of human beings.